Do czego prowadzi „fabrykowanie” harmonii? Odpowiedź na artykuł Katarzyny Szumlewicz pt. Fabrykowanie wiktymizacji. O błędach w badaniach grup szczególnie wrażliwych na przykładzie dokumentu „Sytuacja społeczna osób LGBTA w Polsce. Raport za lata 2019–2020”: What does "fabricating" harmony lead to? Response to Katarzyna Szumlewicz's article entitled Fabricating victimization. About errors in research on particularly sensitive groups based on the example of the document "The social situation of LGBTA people in Poland. Report for 2019–2020" (Biuletyn Kryminologiczny, 2023)
Przedstawiony artykuł ma charakter polemiki naukowej sformułowanej przez autorki i autorów wobec tekstu Katarzyny Szumlewicz pt. „Fabrykowanie wiktymizacji. O błędach w badaniach grup szczególnie wrażliwych na przykładzie dokumentu „Sytuacja społeczna osób LGBTA w Polsce. Raport za lata 2019–2020”. W tekście artykułu odpowiedziano na główne zarzuty stawiane zrealizowanemu autorów/autorki badaniu oraz przygotowanemu raportowi, posiłkując się aktualną literaturą przedmiotu. Podjęta polemika i dyskusja naukowa obejmują wątki odnoszące się m.in. do pojęcia mikroagresji, tożsamości płciowej i orientacji seksualnej, a także refleksje związane z metodologią i etyką badań społecznych.The presented article is a scientific polemic formulated by the authors against the text by Katarzyna Szumlewicz entitled “The fabrication of victimization. On errors in the research of particularly sensitive groups on the example of the document "The social situation of LGBTA people in Poland. Report for the years 2019-2020”. The text of the article answers the main allegations against the authors of the research carried out and the prepared report, using the current literature on the subject. The undertaken polemics and scientific discussion cover topics related to, among others, to the concept of microaggression, gender identity and sexual orientation, as well as reflections related to the methodology and ethics of social research.